A HEALTHY LIFESTYLE IN STUDENT YOUTH AND ITS FORMATION (World Bulletin of Public Health, 2024)
The article presents the results of studying the concepts, knowledge and skills of students of an educational institution about a healthy lifestyle. Despite the fact that students have a healthy lifestyle knowledge, 44.5% do not follow it. One of the factors that determine human health is lifestyle, the proportion of which is 50-60%. Therefore, the formation of healthy lifestyle skills in young people is important in the Prevention of various chronic diseases in the future.
Keywords: Healthy lifestyle; students; nutrition; physical activity